1986
DOI: 10.1073/pnas.83.10.3460
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 induces endothelial cell procoagulant while suppressing cell-surface anticoagulant activity.

Abstract: Previous studies demonstrated that endothelial cells participate actively in both anticoagulant and procoagulant reactions. Although anticoagulant mechanisms predominate on the surface of quiescent endothelial cells, perturbed endothelial cells can promote coagulation through the coordinated induction of procoagulant activity and suppression of anticoagulant mechanisms. Purified recombinant interleukin 1 was infused intravenously into rabbits and coagulant 'properties of the native aortic endothelium were subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
247
1
3

Year Published

1990
1990
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 542 publications
(260 citation statements)
references
References 32 publications
9
247
1
3
Order By: Relevance
“…15 In recent years, however, it became evident that TF has additional biological functions apart from activating coagulation. One of the first indications for a nonhemostatic function of TF was its characterization as an immediate early gene that can be induced during cell division 16 and in response to pathophysiologically relevant stimuli, such as cytokines, 17 growth factors, 18 oxidized LDL, 19 and oxygen free radicals. 20 An exciting recent development in TF biology was the demonstration that this protein, a member of the cytokine receptor superfamily, can function as a true signaling receptor.…”
Section: Discussionmentioning
confidence: 99%
“…15 In recent years, however, it became evident that TF has additional biological functions apart from activating coagulation. One of the first indications for a nonhemostatic function of TF was its characterization as an immediate early gene that can be induced during cell division 16 and in response to pathophysiologically relevant stimuli, such as cytokines, 17 growth factors, 18 oxidized LDL, 19 and oxygen free radicals. 20 An exciting recent development in TF biology was the demonstration that this protein, a member of the cytokine receptor superfamily, can function as a true signaling receptor.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study showed that oxidized LDL reduced TM expression on endothelial cell surfaces, 15) and TM mRNA expression was reduced by the pro-inflammatory cytokines IL-1 16) and TNF. 17) Therefore, TM expression may be reduced by these atherogenic pro-inflammatory cytokines on the endothelial cells of atherosclerotic coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…However, when exposed to thrombin, cytokines, or LPS, endothelial cells synthesize and express tissue factor at their surface (Nawroth et al, 1986;Mackman, 1997). Once coagulation has been initiated, endothelial cells promote thrombi activation since the activity of factor Xa (generated by tissue factor plus factor VII) is locally enhanced by promotion of binding with its cofactor Va at adjacent Xa and Va receptors on the endothelial cell surface (Davie et al, 1991;Chen et al, 2001).…”
Section: Coagulation and Fibrinolysismentioning
confidence: 99%